The Effect of Organizational Culture and Organizational Commitment on Performance in Government Agencies X - Hidayat, Arif Rahmat (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this study was to explain the effect of Organizational Culture and Organizational Commitment on Performance at Government Agency X. The population in this study were employees of Government Agency X. The analytical tool used is path analysis with SEM (structural equation modeling) method using SmartPLS. The results showed that Organizational Culture has a positive and significant effect on Performance. Organizational Commitment has a positive and significant effect on performance. Organizational Culture and Organizational Commitment have a significant effect together. Therefore, it is important for company leaders to pay attention to Organizational Culture and Organizational Commitment in order to improve Performance.